Evaluation of The Accuracy and Success of Providing Smart Indonesia Card Assistance - Independent Lectures at XYZ University and ABC University - Saputra, Prabetti Amriyadi; Sailah, Illah; Kuswanti, Heny (Ridwan Institute, 2024)
The provision of the Indonesia Smart Card-Independent College (KIP-KM) has been running since 2021. The current condition of KIP-KM is decreasing in numbers in almost all regions of Indonesia. Some universities still often change recipients and stop giving KIP-KM. Until now there is no information about the accuracy and success of the program, so there needs to be an academic study. This research aims to evaluate the implementation of providing KIP-KM to poor students in private universities under the guidance of LLDIKTI Region XII. XYZ University and ABC were chosen because these two universities are the largest private universities in LLDIKTI Region XII and have a large KIP-KM quota in Maluku. This research is qualitative research with analysis techniques Miles and Huberman (2014). Data collection using documentation and interviews. Data were analyzed using the CIPP evaluation model. The results showed that: 1) The KIP-KM program is contextually not entirely appropriate but has been successful; 2) The input is correct, but not yet fully successful; 3) The process is correct, but not yet fully successful; 4) Product-wise it is correct and successful.